ROLE OF RELIGION MOTIVES AND BRAND IMAGE TOWARDS CONSUMER SATISFACTION AND CONSUMER LOYALTY OF ISLAMIC BANKING - Ayuni, Risca Fitri; Hussein, Ananda Sabil; Handrito, Radityo (Accounting Department,, 2015)
Islamic/ sharia labelling on every product have mass impact on consumer behavior on consumption. Shari’ label originally created to capture niche segment who very concern on islamic value of banking. In fact, non-moslem also interested and become loyal consumer on those product. This study address to answer what is role of religion motibes and brand image through satisfaction and loyalty in banking industry. Study found that religion motives (sharia principles) impacts brand image and plays significant role on determining consumer satisfaction and loyalty.Keyword: Islamic banking, religion, brand image, satisfaction, loyalty